Bruce Springsteen : American Poet and Prophet. - Deardorff, Donald L., II (Scarecrow Press, 2013)
Bruce Springsteen: American Poet and Prophet by literary critic Donald L. Deardorff II classifies and explains Springsteen's remarkable reception as it evolved from small beginnings in the Jersey shore bars of the 1970s to worldwide fame today. This book thoughtfully considers the trenchant commentary Springsteen's albums make on the mythology of the American Dream, working-class concerns, the changing character of American masculinity, the relationship between Americans and their government, the importance of social justice, and the evocation of an American spirit.